2011
DOI: 10.1021/jf202426k
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Modulates MED28 (Magicin/EG-1) Expression and Inhibits Epidermal Growth Factor (EGF)-Induced Migration in MDA-MB-231 Human Breast Cancer Cells

Abstract: Resveratrol and pterostilbene exhibit diverse biological activities. MED28, a subunit of the mammalian Mediator complex for transcription, was also identified as magicin, an actin cytoskeleton Grb2-associated protein, and as endothelial-derived gene (EG-1). Several tumors exhibit aberrant MED28 expression, whereas the underlying mechanism is unclear. Triple-negative breast cancers, often expressing epidermal growth factor (EGF) receptor (EGFR), are associated with metastasis and poor survival. The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…Moreover, resveratrol has been demonstrated to modulate MED28 (magicin/EG-1) expression and inhibit epidermal growth factor (EGF)-induced migration in MDA-MB-231 human breast cancer cells. The role of MED28 in cell migration reinforces the importance of this multifaceted protein and raises the possibility of clinical application in a combination therapy of resveratrol and MED28 suppression in breast cancer cells (44). Another recent study revealed the effects of resveratrol on cyclooxygenase-1 and -2, NF-κB, MMP-9 and sirtuin 1 mRNA expression in the hearts of streptozotocin-induced diabetic rats (45).…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, resveratrol has been demonstrated to modulate MED28 (magicin/EG-1) expression and inhibit epidermal growth factor (EGF)-induced migration in MDA-MB-231 human breast cancer cells. The role of MED28 in cell migration reinforces the importance of this multifaceted protein and raises the possibility of clinical application in a combination therapy of resveratrol and MED28 suppression in breast cancer cells (44). Another recent study revealed the effects of resveratrol on cyclooxygenase-1 and -2, NF-κB, MMP-9 and sirtuin 1 mRNA expression in the hearts of streptozotocin-induced diabetic rats (45).…”
Section: Discussionmentioning
confidence: 87%
“…A subunit of the mammalian mediator complex for transcription called MED28, the overexpression of which could increase migration, was also reduced by resveratrol through the EGFR/ PI3K signaling pathway (72). The in vivo research of breast cancer also confirmed the effect of inhibition of MMP-9 in the anti-metastasis process.…”
Section: Resveratrol Affects the Expression And Activity Of Mmpsmentioning
confidence: 80%
“…It has been suggested that resveratrol plays a role in inhibiting the expression of MMP (mainly MMP-9) [174][175][176][177] and angiogenesis markers such as VEGF, EGFR or FGF-2 [79,178]. Resveratrol reduced the phorbo-12-myristate 13-acetate (PMA)-induced migration and invasion ability of liver cancer HepG2 and Hep3B cells.…”
Section: Anti-tumor-progression Activitymentioning
confidence: 99%